Effects of Interest Inducing Activities Programs on the Attention and Self-efficacy of School-aged Children (Medico Legal Update, 2020)
Background/Objectives: The purpose of this study is to investigate the effects of interest inducing activities program (IIAP) within three type on attention and self-efficacy in school-aged children.Method/Statistical Analysis: This study was conducted on 22 children except 3 out of 25 elementary school children registered in the center In addition,they were classified into craft activities, reading activities, physical activities. To determine the change in the child’s attention and self-efficacy, Harris & Harris Grid Test, and self-efficacy questionnaire are used.Findings: There was no statistically significant difference in attention through IIAP in three groups (p>0.05). In the self-efficacy, there was a statistically significant difference among the groups (p0.05).Improvements/Applications: We suggest it is important to develop programs for voluntary participation and children’s attention and self-efficacy